Household Conflict In The Novel Kembali Bebas By Sasa Ahadiah: A Sociological Literary Study - Widyawati Bagoe; Sitti Rachmi Masie; Herson Kadir (Raja Zulkarnain Education Foundation, 2026)
This study aims to analyze the forms of domestic conflict in Sasa Ahadiah’s novel Kembali Bebas using a sociological approach to literature. Household conflicts are a social phenomenon often represented in literary works, yet there remains limited research that systematically examines them in contemporary Indonesian novels. The novel Kembali Bebas (2023) was chosen because it deeply illustrates the dynamics of conflict between the characters Tata and Ibra, who have been building a household for more than 28 years. This research uses a descriptive qualitative method with a sociological literary approach. The research data consists of dialog excerpts and narratives that contain indicators of domestic conflict, collected through reading and note-taking. Data analysis was conducted by identifying, classifying, and describing the data based on Awaru’s (2021) family conflict theory. The research findings identified three forms of domestic conflict in the novel. First, arguments characterized by a high tone of voice and shouting at each other, physical gestures of anger, and discussions about divorce. Second, not reprimanding each other, manifested through ignoring the partner’s invitation to talk and remaining silent during conflicts. Third, not respecting each other, reflected in belittling remarks toward the partner and ignoring mutual agreements. These three forms of conflict are interconnected and indicate that ineffective communication and power imbalance are the main roots of marital discord. This research contributes to the development of literary sociology studies, particularly in the analysis of family conflicts in contemporary Indonesian popular literature. The findings of the study show that domestic conflicts in the novel do not appear suddenly, but develop due to the accumulation of problems that last for a long time. The novel Kembali Bebas not only functions as an entertainment work, but also as a medium of social reflection on the importance of building harmonious and equal family relationships.